On Linial’s Conjecture for Split Digraphs - Sambinelli, Maycon; da Silva, Cândida Nunes; Lee, Orlando (Anais do Encontro de Teoria da Computação (ETC), 2016)
In this paper we show that Linial’s Conjecture holds for two classes of split digraphs, namely the spider digraphs and the k-loose digraphs.